Facile ultrasonic preparation of a polypyrrole membrane as an absorbent for efficient oil-water separation and as an antimicrobial agent - Moorthy Maruthapandi; Arumugam Saravanan; Shanmugasundaram Manoj; John H.T. Luong; Aharon Gedanken (Ultrasonics Sonochemistry, 2021)
Polypyrrole (PPY) spherical particles synthesized using carbon dots as an efficient catalyst were strongly embedded on fluorinated nonwoven fabric by ultrasonication to form a membrane with high hydrophilicity. An optimal amount of PPY adhered to the membrane after 30 min of sonication enhanced the overall membrane area with high hydrophilicity. Oil with high hydrophobicity was repelled by the resulting membrane, whereas water was freely penetrated and diffused from the membrane. The membrane exhibited good reusability and efficiency for the recovery of oil from a cooking oil–water mixture within 30 s. The incorporation of PPY in the fluorinated fabric imparts significant antibacterial properties against two common pathogens, Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive). The anti-biofouling membrane could pave the way for its potential application to separate spilled oil from contaminated waters, comprising different microorganisms and living species. The novelty of this manuscript is described in a new system, the fabrication of PPY membranes with two important properties: biocidal and oil/water separation.